Encounters between Public Relations Education and the Profession in Andalusia: Analysis of Undergraduate Studies - Ruiz-Mora, Isabel; Guerrero-Navarro, Daniel; Álvarez-Nobell, Alejandro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The teaching of public relations faces the challenge of competency-based learning in a professional context characterised by the new challenges of the sector. In this context, we review the state of public relations teaching in Andalusian universities in order to determine its suitability in accordance with professional requirements. The methodology employed includes a documentary review of professional reports and a content analysis of the syllabuses, reviewing professional competencies, teaching methodologies and evaluation. To find out whether public relations training in Andalusia meets the needs of the professional sector.